"Free, Compulsory and (Not) Secular": The Failed Idea in Australian Education*. (10th October 2012) - Byrne, Catherine
<x xml:space="preserve">Abstract</x> The nineteenth century radically transformed education from a church function to a state duty. During the early to late 1800s, Australian legislators debated the foundations of education for their new society. Decades of acrimonious argument, and sustained (but failed) attempts to create a workable denominational system led the colonies to explore more radical options. To minimize religious division, Australia's proposal was for public education to be "free, compulsory and secular." New South Wales legislated these then politically progressive principles in the Public Instruction Act of 1880, following Victoria in 1872, and Queensland and South Australia in 1875. No state defined the term "secular" and each interpreted it differently. Prolonged, ambiguous applications of the secular principle continue to create confusion and division today. This article examines constructions of the "secular" in education and compares the approaches of Henry Parkes in New South Wales and George Higinbotham in Victoria. It follows the erosion of secular intent in public and parliamentary debates from early settlement to 1880.